Sedimentologia e estratigrafia isotópica de carbono e oxigênio do Grupo Vazante na região de Morro Agudo, Paracatu/MG - Marcus Paulo Sotero (2019)
Vazante Group rocks outcrop in the northwest of Minas Gerais state, in a continuous belt of approximately 250 km, from the region of Vazante city, in the south, to Unaí city, in the north. It comprises a clay-carbonate sequence of approximately 5 km in thickness. In the region of Morro Agudo (Vazante Norte Group) is composed of twelve sedimentary facies and four facies associations (AFs), which indicate deposition in a carbonate-siliciclastic mixed marine passive margin setting. The sedimentary facies were described in six drill holes, and of two holes, were sampled at high resolution (3 m) to evaluate the preservation of the samples, construction of the isotopic curves (δ13C and δ18O), and regional stratigraphic correlation. The most basal association (AF01) represents sedimentation in a deep marine platform of low slope angle, in a regime of marine transgression. After the maximum flood surface, in the highstand systems tract, the AF02 was deposited in a reef setting with a barrier at the platform edge. The fall of the relative sea level led to the deposition of the AF03 in a forced regressive systems tract. The AF02 potentially served as source area for the carbonaceous diamictites of AF03. The return of the rise of the relative sea level provided the deposition of AF04 and AF03 rocks in a more distal position. The AF04 were deposited in carbonate marine platform. The observed stacking pattern suggests that the deposition of all units occurred progressively, in an almost complete cycle of rising relative sea level (transgressive and highstand systems tracts), of falling sea level (forced regressive systems tract), and return of rising relative sea level (lowstand system tract). Despite the pervasive dolomitization of the Vazante Group carbonates (Mg/Ca >0,5) and frequent hydrothermalism, most of the samples can be classified as little altered dolostone, with some exceptions, generally associated with the Serra do Landim Formation or the mineralized range at the top of the Morro do Calcário Formation. The values of δ13C and δ18O obtained in dolomite rocks range between -4,57 and 2,52 ‰VPDB and 11,07 and -1,63 ‰VPDB, respectively. The isotopic profiles of δ13C are characterized by predominantly positive values for the Morro do Calcário Formation followed by an important negative incursion above the diamictito facies, and positive trend towards the top. The best chemostratigraphic marker present in all regions is the strong negative incursion at the base of the Serra da Lapa Formation. The isotopic results of the Vazante Group North samples are consistent with the values of Proterozoic carbonates and isotopic curves can be correlated with other regions of Vazante group. Based on this correlation, it can be inferred that the North and South portions of the Vazante Group were deposited in the same basin, or in basins with some connection, possibly separated (partly) by the Rio Escuro elevation.